2022
DOI: 10.1002/lary.30273
|View full text |Cite
|
Sign up to set email alerts
|

Early Neurocognitive Function With Propofol or Desflurane Anesthesia After Laser Laryngeal Surgery With Low Inspired Oxygen

Abstract: Purpose The effects of general anesthetics on cognitive impairment are unclear and complicated. Laser laryngeal surgery (LLS) requires the administration of low levels of oxygen, which may increase the risk of desaturation and brain function impairment. This prospective randomized trial aimed to compare the effects of desflurane and propofol‐based general anesthesia on the occurrence of early postoperative cognitive decline in elderly patients undergoing LLS. Methods Seventy‐three patients classified as Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…As seen by their lower MMSE scores compared to individuals who did not have delayed neurocognitive recovery, it is interesting to note that these patients had worse cognitive performance ( 29 ). Additionally, these individuals spent longer in the hospital, which is consistent with other findings ( 30 , 31 ). Age, Mini-mental State Examination score, State-anxiety inventory score, Trait-anxiety inventory score, duration of anesthesia, and length of hospital stay were found to be significant predictors of delayed neurocognitive recovery in the analysis of Univariate Logistic regression.…”
Section: Discussionsupporting
confidence: 92%
“…As seen by their lower MMSE scores compared to individuals who did not have delayed neurocognitive recovery, it is interesting to note that these patients had worse cognitive performance ( 29 ). Additionally, these individuals spent longer in the hospital, which is consistent with other findings ( 30 , 31 ). Age, Mini-mental State Examination score, State-anxiety inventory score, Trait-anxiety inventory score, duration of anesthesia, and length of hospital stay were found to be significant predictors of delayed neurocognitive recovery in the analysis of Univariate Logistic regression.…”
Section: Discussionsupporting
confidence: 92%
“…TIVA has been suggested to have potential neuroprotective effects. Studies have demonstrated that some intravenous agents, like propofol, may reduce the inflammatory response and oxidative stress in the brain, potentially minimizing the risk of POCD (Qiao et al, 2023). Inhalational agents like desflurane and sevoflurane, on the other hand, have been associated with neuroinflammation and oxidative stress, possibly increasing the risk of cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%